The THE EFFECT OF PROFITABILITY, FIRM SIZE, EQUITY OWNERSHIP AND FIRM AGE ON FIRM VALUE (LEVERAGE BASIS): Evidence from the Indonesian Manufacturer Companies - Lambey, Robert (Archives of Business Research, 2021)
This study examines the effect of profitability, firm size, equity ownership and firm age on firm value. This is a quantitative research study. Samples were taken from 65 manufacturing companies that go-public and listed at the Indonesian Stock Exchange from 2012 to 2019. Data were analysed by Path Analysis with Amos SPSS 24. Findings indicate that profitability and firm size influence firm value significantly and positively. Whilst, firm value is affected by profitability and firm size, it is not influenced significantly and positively by firm age. On the other hand, owner’s equity provides a negative effect to firm value.